(untitled) (Medical Forum Monthly, 2024)
Objective: The purpose of this study was to assess the extent to which mental health support influences the experience of Chronic Pelvic Pain (CPP) in a sample of 110 patients. Study Design: A randomized controlled study Place and Duration of Study: This study was conducted at the Department of Psychiatry & Gynae & Obs, Mardan Medical Complex (MMC), Mardan, Pakistan from 11th May 2020 to 10th October 2020. Methods: This study recruited 110 patients to take part in the study and all of them had CPP diagnosis confirmed. The participants were divided into two groups: Group A (n=55) serving as the control group, received standard medical treatment for CPP, while Group B also received standard medical treatment for CPP but augmented with mental health support through CBT and counseling sessions. The study took six months hence the appropriateness in the selection of the timeframe for the study. Results: 110 patients were recruited in the study, 100 patients complied with the six-month follow and we had 50 patients in group A and group B respectively. The average age of the participants was 42.7±10.5 years, and 76% of the participants were females. After the three months of follow-up, the result of Group B was significantly decreased compared with Group A in the aspect of mean VAS score of pain (4.8 vs 6.1, p<0. 01). Conclusion: The authors note that implementing mental health as part of the treatment program in patients with CPP enhances efficacy in pain therapy.